2009
DOI: 10.3892/or_00000278
|View full text |Cite
|
Sign up to set email alerts
|

PTEN expression controls cellular response to cetuximab by mediating PI3K/AKT and RAS/RAF/MAPK downstream signaling in KRAS wild-type, hormone refractory prostate cancer cells

Abstract: Abstract. Overexpression of epidermal growth factor receptor (EGFR) and mutation of pten tumor suppressor gene in human cancer cells leads to activated EGFR downstream signaling including PI3-kinase/AKT (PI3K/AKT) and/or mitogen-activated protein kinases (RAS/RAF/MAPK) and have been linked to resistance to anti-EGFR targeted therapies. Cetuximab is a chimeric IgG1 monoclonal antibody that binds the EGFR with high specificity and have been developed as promising therapeutic anticancer treatments in several soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Inactivation of PTEN is a key event in tumorigenesis and tumor development, and in fact it has the highest frequency of mutation in cancer after the P53 gene [6]. Currently, the tumor suppressing mechanism of the PTEN gene likely involves several candidate pathways, including the FAK pathway [7], the MAPK pathway [8, 9], and the PI3K/AKT pathway [10, 11]. Currently, the PI3K/AKT pathway is regarded as the key pathway by which PTEN exerts its antioncogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of PTEN is a key event in tumorigenesis and tumor development, and in fact it has the highest frequency of mutation in cancer after the P53 gene [6]. Currently, the tumor suppressing mechanism of the PTEN gene likely involves several candidate pathways, including the FAK pathway [7], the MAPK pathway [8, 9], and the PI3K/AKT pathway [10, 11]. Currently, the PI3K/AKT pathway is regarded as the key pathway by which PTEN exerts its antioncogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, EGFRvIII is a mutant form of EGFR that is expressed in 40% of head and neck cancers [34] and is believed to be involved in cetuximab resistance [35]. The tumor suppressor gene PTEN blocks the PI3K/AKT signal transmission pathway, and previous studies have suggested that the absence or diminished expression of PTEN contributes to cetuximab resistance [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of PTEN in prostate cancer inhibits PI3K/Akt signaling. Then, a significant decrease occurs in expression levels of GSK‐3β, P70S6 kinase and ERK1/2 as downstream targets, leading to apoptotic cell death in prostate tumor and improving response to cetuximab (Bouali et al 2009). As it was mentioned, ADT is employed for prostate cancer suppression, but there are reports of resistance.…”
Section: Pi3k/akt In Therapy Resistancementioning
confidence: 99%